Olive oil and its phenolic components and their effects on early- and late-stage events in Carcinogenesis - Gill , Chris I.R.; Hashim , Yumi Zuhanis Has-Yun; Servili , Maurizio; Rowland , Ian R. (Elsevier, Inc., 2010)
108.1 INTRODUCTION Olive oil is a key component in the Mediterranean-style diet ( Stark and Madar, 2002 ). It has been recognized as having great potential to prevent the onset of oxidativedamage- associated diseases such as cancer, aging and cardiovascular problems. The Mediterranean diet, for example, is associated with lower incidence of colorectal cancer and it has been estimated that the incidence of colorectal cancer among the developed Western countries’ population could be reduced by 25% if they were to consume the Mediterranean-style diet ( Trichopoulou et al., 2000 ). Apart from the high monounsaturated fatty acid content, squalene, vitamin E and phenolic compounds are also present in olive oil and have been suggested to have roles in modulating cancer risk; this area was reviewed in detail by Hashim et al. with respect to colorectal cancer who indicated a number of potential mechanisms through which olive oil and its components may exert an effect ( Hashim et al., 2005 ). The hydrophilic phenols are the most abundant natural antioxidants of virgin olive oil (VOO), while the phenolic alcohols and acids, the major classes of hydrophilic phenols found in VOO, include secoiridoids, flavonoids and lignans. Secoiridoids, like the aglycon derivatives of oleuropein, demethyloleuropein and ligstroside, are the most abundant VOO phenolic antioxidants present in olive fruit. These phenolic compounds, in particular, may act as anticarcinogens through several mechanisms such as quenching or preventing the formation of reactive oxygen species, inhibiting arachidonic acid metabolism leading to reduced proinflammatory or mitogenic metabolites and modulating cancer-related genes in favor of inhibition of carcinogenesis ( Yang et al., 2001 ) ( Figure 108.1 ).